Alterations in affective behavior during the time course of alcohol hangover - Karadayian, Analia Graciela (2013)
Alcohol hangover is a temporary state described as the unpleasant next-day effects after binge-like drinking. Hangover begins when ethanol is absent in plasma and is characterized by physical and psychological symptoms. Affective behavior is impaired during the acute phase of alcohol intoxication; however, no reports indicate if similar effects are observed during withdrawal. The aim of this work was to study the time-extension and possible fluctuations in affective behavior during a hangover episode. Male Swiss mice were injected i.p. either with saline (control group) or with ethanol (3.8. g/kg BW) (hangover group). Anxiety, fear-related behavior and despair phenotype were evaluated at a basal point (ZT0) and every 2. h up to 20. h after blood alcohol levels were close to zero (hangover onset). Also, anhedonia signs and pain perception disabilities were studied. Mice exhibited an increase in anxiety-like behavior during 4. h and 14. h after hangover onset when evaluated by the elevated-plus maze and open field test respectively (p<. 0.05). Fear-related behavior was detected in hangover animals by the increase of freezing and decrease of line crossings and rearing frequency during 16. h after hangover onset (p<. 0.001). Depression signs were found in hangover mice during 14. h (p<. 0.05). Hangover mice showed a significant decrease in pain perception when tested by tail immersion test at the beginning of hangover (p<. 0.05). Our findings demonstrate a time-extension between 14 and 16. h for hangover affective impairments. This study shows the long lasting effects of hangover over the phase of ethanol intoxication. © 2013 Elsevier B.V.